Sedentary lifestyle may contribute to the risk of depression during the COVID-19 pandemic: A snapshot of Hungarian adolescents - Berki, László Tamás; F. Pikó, Bettina (European Journal of Mental Health, 2021)
Background: Social exclusion usually contributes to an increased vulnerability to mental health problems and risky health behaviors. This study aims to identify the role of health behavior in the increased risk of depressive symptoms among adolescents during the coronavirus pandemic in Hungary.Methods: A total of 705 high school students participated in our study (M = 15.9 years; SD = 1.19). The self-administered questionnaire included items about sociodemographics, eating habits, physical activity, sedentary behavior, and substance use. Depressive symptoms were measured using the short version of the Child Depression Inventory. Descriptive statistics and binary logistic regression were used to analyze our results.Results: Daily fruit and vegetable consumption was reported by 21.7% and 22.4% of respondents, respectively. The proportion of the respondents reporting daily sweets consumption stood at 13.2%, daily soft drinks consumption was 12.3%, and daily energy drink consumption tallied to 4.5%. More than one-third of the sample (35.5%) reported having breakfast every school day, which rose to 68.1% of the sample reporting breakfast on both weekend days. The rate of students engaged in daily physical activity was 6.5%, while 86.1% of them reported more than four hours screen time in a day. In addition, despite the mandatory confinement, a notable percentage of adolescents engaged in substance use. Consistent with previous studies, girls had a higher risk of depression. Low levels of physical activity and high levels of screen time – as well as alcohol and drug use – were associated with a high risk of depression.Conclusions: We believe our study provided useful information on adolescent health behaviors that can lead to adolescents’ depression, and that maintaining physical activity can prevent it even in these unusual circumstances.